Environmental safety of phytogenic fields formation on coal mines tailings - Popovych, Vasyl; Bosak, Pavlo; Petlovanyi, Mykhailo; Telak, Oksana; Karabyn, Vasyl; Pinder, Volodymyr (My University, 2021)
Objective of the study is to research peculiarities of phytogenic fields formation of natural and artificial plantations of shrub and ruderal vegetation on coal mining waste heaps within the Novovolynsk mining area (Ukraine). The biometric analysis of the growth of artificial plantations on tailings has been carried out applying forest inventory methodology, which involves laying temporary experimental areas, measuring the diameter of tree species at a height of 1.3 m, the total height of trees and the parameters of crowns. Variation was applied to study the spatial structure of vegetation on reclaimed and damped waste heaps. The models of artificial phytocenoses and ameliorants on waste heaps of coal mines, which are formed during forest reclamation, have been described. The paper presents an analysis of forest inventory characteristics of the crops phytocenosis on waste heaps. The spatial structure of phytogenic fields basing on variation of the most common species in natural and artificial plantations on waste heaps has been established. This allows us to select an assortment of species to conduct effective vegetative reclamation on the surface of tailings. The article presents result of studies on the formation of phytogenic fields on waste heaps of coal mines, which presuppose formation of aggregations. It has been proved that formation of phytogenic fields is inextricably connected with vegetative reclamation. The conducted research of the origin and distribution of phytogenic fields makes it possible to assess the degree of suitability of tailings for afforestation, regardless of the country in which they are formed. Research of phytogenic fields on tailings and waste heaps of coal mines will improve bioindication research methodology for studying forest crops on their surface and suggest innovative methods of handling. In particular, it is possible to raise the level of environmental safety and aesthetics of the devastated territories, and to reduce cost of vegetative reclamation.
Keywords: environmental safety, phytogenic field, coal mine, tailing, phytocenosis, forest crops, reclamation